Early life socio-economic position and later alcohol use: birth cohort study. - Melotti, Roberto; Lewis, Glyn; Hickman, Matthew; Heron, Jon; Araya, Ricardo; Macleod, John (Addiction, 2013)
Aims To investigate associations between socio-economic position in early life and later alcohol use and problem use among male and female adolescents. Design Birth cohort study. Setting South West England. Participants A total of 2711 girls and 2379 boys with one or more measures of alcohol use or problem use at age 15 years. Measurements Exposure measures were highest parental social class, maternal education and household disposable income (all maternal self-report before school-age); outcome measures were heavy typical drinking, frequent drinking, regular binge drinking, alcohol-related psychosocial problems and alcohol-related behavioural problems. Findings Alcohol use and related problems were relatively common amongst adolescent girls and boys. Boys were slightly more likely to report frequent drinking and girls were slightly more likely to drink heavily and to experience alcohol-related psychosocial problems. Higher maternal education appeared protective in relation to alcohol-related problems, particularly among boys. Higher household income was associated with greater risk of alcohol use and problem use, most apparently among girls. Conclusions Children from higher-income households in England appear to be at greater risk of some types of adolescent alcohol problems, and these risks appear different in girls compared to boys. Childhood social advantage may not generally be associated with healthier behaviour in adolescence.